Improving Engineering Students’ Ability in Writing Descriptive Text Using GBA - Sri Hastuti - (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2020)
Writing is one of the English skills needed by engineering students to express their knowledge and skill relating to their major. Based on the researcher’s teaching experience, students still have low ability in writing. In this research, the researcher made an effort to improve their descriptive writing text in an engineering context. The aim was to increase their ability to make descriptive text using Genre Based Approach. The research was carried out in the Road and Bridge Planning Study Program in the Civil Engineering Department of a Polytechnic in Indonesia. The sample included the students of the study program. The design of the research was the Pre Test-Post Test Design. The result shows that the students’ writing ability can be increased by applying the GBA teaching procedure with adjustment to their major and level of English capability. This strategy can be used as an alternative to improve students’ ability to make descriptive texts in an engineering context.